2023
DOI: 10.3389/fmicb.2023.1208301
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilariasis mouse models for heartworm preclinical research

Abstract: IntroductionDirofilariasis, including heartworm disease, is a major emergent veterinary parasitic infection and a human zoonosis. Currently, experimental infections of cats and dogs are used in veterinary heartworm preclinical drug research.MethodsAs a refined alternative in vivo heartworm preventative drug screen, we assessed lymphopenic mouse strains with ablation of the interleukin-2/7 common gamma chain (γc) as susceptible to the larval development phase of Dirofilaria immitis.ResultsNon-obese diabetic (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Vehicle and 10 mg/kg ABZ control groups were also included ( Figure 5A ). Using previously established FISH staining with Wolbachia- specific 16S rRNA probes (Walker et al, 2021 ; Marriott et al, 2023 ), we visualised and quantified Wolbachia loads both in hypodermal chords and ovaries in female worms from control and different drug treatment groups. Previous studies have shown that the ovaries have the highest density of germline Wolbachia populations (Bakowski et al, 2019 ) and are also the only tissue site in mature adult worms containing proliferating cells (Foray et al, 2018 ); thus, they serve as an ideal tissue to compare against hypodermal chords.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle and 10 mg/kg ABZ control groups were also included ( Figure 5A ). Using previously established FISH staining with Wolbachia- specific 16S rRNA probes (Walker et al, 2021 ; Marriott et al, 2023 ), we visualised and quantified Wolbachia loads both in hypodermal chords and ovaries in female worms from control and different drug treatment groups. Previous studies have shown that the ovaries have the highest density of germline Wolbachia populations (Bakowski et al, 2019 ) and are also the only tissue site in mature adult worms containing proliferating cells (Foray et al, 2018 ); thus, they serve as an ideal tissue to compare against hypodermal chords.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we determined that via depletion of Wolbachia in the mf-stage, AWZ1066S can also block the development of Brugia in the mosquito vector via a deficit in Wolbachia, inhibition of mf chitinase production and failure to exsheath in the insect midgut (Quek et al, 2022). Most recently, we have determined 90% anti-Wolbachia activity of AWZ1066S against developing larvae of the veterinary filaria, Dirofilaria immitis, following 2-day exposures in vivo, extending the potential use-case of this new class of anti-Wolbachia therapeutic from human to veterinary medicine (Turner et al, 2020;Marriott et al, 2023). In this study, compared with a 100 mg per day human equivalent dose exposure of doxycycline (Sharma et al, 2016), which requires 6 weeks in a SCID model of brugian filariasis to mediate >90% anti-Wolbachia activity, we further established the minimum AWZ1066S dose time frame of 5 days which could sustainably deplete Wolbachia to a similar or >99% threshold when sufficient bi-daily dose-exposures were applied against mature B. pahangi in gerbils (Figures 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aim to establish a murine model of M. perstans based on the knowledge of the established animal models of onchocerciasis, lymphatic filariasis and loiasis. Immunocompromised mouse strains that lack adaptive immunity pathways like RAG2 −/− ( 27 , 28 ), IL-4/5 −/− ( 32 ) and NSG strains ( 26 , 36 ) have been proven suitable for human filarial infections and recently, NSG mice have been also proven to be susceptible to infection with the dog heartworm Dirofilaria immits ( 47 , 48 ). Indeed, a 62-66% L3 recovery rate could be obtained upon Loa loa L3 inoculation, whereas M. perstans and O. volvulus L3 were absent in all immunocompromised mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established mouse models for L4 development in D. immitis using NOD-, NSG-, or NXG immunode cient mice [23,24]. This study proposes a micro laremia model for D. immitis using SCID mice.…”
Section: Discussionmentioning
confidence: 99%